Remote Physiological Data Acquisition: from the human body to electromechanical simulators - Barros, C. (2013)
The problems that health professionals faced may involve engineering practicalities, e.g., the design of efficient devices in physiological specific monitoring activities. Therefore, it is important to know the type and characteristics of the physiological signals and how to acquire them. This paper presents the conceptual model for physiological data acquisition in a new remote didactic environment. This comprises two different approaches: human physiological and electromechanical simulators data acquisition. The insights on the data acquisition system development are described, emphasizing the added value of this new innovative educational tool for biomedical engineering.